Dynamics of contention - McAdam, Doug; Tarrow, Sidney G.; Tilly, Charles (Cambridge studies in contentious politics., 2001)
"Over the past two decades the study of social movements, revolution, democratization and other non-routine politics has flourished. And yet research on the topic remains highly fragmented, reflecting the influence of at least three traditional divisions. The first of these reflects the view that various forms of contention are distinct and should be studied independent of others. Separate literatures have developed around the study of social movements, revolutions and industrial conflict. A second approach to the study of political contention denies the possibility of general theory in deference to a grounding in the temporal and spatial particulars of any given episode of contention. The study of contentious politics are left to 'area specialists' and/or historians with a thorough knowledge of the time and place in question. Finally, overlaid on these two divisions are stylized theoretical traditions - structuralist, culturalist, and rationalist - that have developed largely in isolation from one another." http://www.loc.gov/catdir/description/cam021/2001016172.html